Interaction Between Concrete and FRP Laminate in Structural Members Composed of Reused Wind Turbine Blades Filled with Concrete - Halicka, Anna; Buda-Ożóg, Lidia; Broniewicz, Mirosław; Jabłoński, Łukasz; Zięba, Joanna; Broniewicz, Filip (My University, 2024)
The lifecycle of wind turbine blades is around 20–25 years. This makes studies on the reuse of dismantled blades an urgent need for our generation; however, their recycling is very difficult due to the specific makeup of their composite material. In this study, the authors determined a concept for the reuse of turbine blade sections filled with concrete for geotechnical structures, retaining the walls, piles, or parts of their foundations. Working out detailed structural solutions to the above problem should be preceded by the identification of material parameters. In particular, getting to know the interface stress-strain characteristics is crucial. Therefore, this research focuses on the cooperation between recycled FRP composites and concrete in load-carrying, including experiments and numerical analyses. Regarding the two types of destructive stress, which may occur at the interface under both compression and bending, two types of tests were executed: the ‘push-out test’, modelling the interface’s answer to shear stress, and the ‘pull-off test’, demonstrating the interface’s reaction to normal stress. Additionally, the strength parameters of the materials used were tested. The numerical model for the push-out process was calibrated on the basis of the tests, and this way the shear bond strength and the coefficient of friction between the concrete and the recycled FRP laminate were assessed.
Keywords: wind turbine blade; recycling; FRP laminate; hybrid structural element; concrete; roughness; push-off test; bond strength; en